The problem of the African Intellectual: Yesterday and Today (La problématique de l'intellectuel en Afrique noire, hier et aujourd'hui) - (:unkn) unknown (My University, 2014)
The issue of the African intellectual has a current relevance, because of the status of the intellectual in the modern African states. Does the African intellectual only represent the continuation of the western cultural and intellectual imperialism in Africa or is he/she the person who can lead his community to a real freedom? How is it possible to define and to characterize the African intellectual today? How is it possible to envision educational systems in Africa, able to produce intellectuals to serve Africa in a globalized world? The article examines these questions from a historical perspective and underlines the distinction between being a graduate and being an intellectual. It suggests a reconsideration of the role of the school and education in Africa. Education in Africa needs to be related to the African context and the challenges faced by African peoples, rather than to replicate western paradigms, in order to train educated Africans for the sake of 21st century’s Africa.
Keywords: African Research